Main influencing factors of terrestrial evapotranspiration for different land cover types over the Tibetan Plateau in 1982–2014 - Li, Xia; Pan, Yongjie; Zhao, Cailing (Frontiers in Environmental Science, 2024)
Terrestrial evapotranspiration (ET) over the Tibetan Plateau (TP) has important implications for the global water cycle, climate change and ecosystem, and its changes and driving factors have drawn more and more attentions. Previous researches have less quantified the effects and identified the pathways of influencing factors on ET over different land surface types. In this study, we analyze the spatiotemporal distribution and variation of ET over the TP in 1982–2014 based on multiple datasets. Furthermore, the effects of each influencing factor on ET are quantified over different land surface types, and the major influencing factors and their affecting pathways are identified using the Structure Equation Modeling (SEM), which is a statistical method used to analyze relationships among multiple variables. Results show that the climatology of ET decreases from the southeastern to northwestern TP, with the maximum spatial averaged value of 379.979±0.417 mm a-1 for the fifth generation of European Reanalysis (ERA5), and the minimum of 249.899±0.469 mm a-1 for the Global Land Data Assimilation System (GLDAS). The most significant differences among the ET datasets mainly occur in summer. The annual ET averaged over the TP presents increased trend in 1982–2014 as shown by all of the ET datasets. However, there are larger discrepancies in the spatial distribution of the increased trend for these datasets. The assessment result shows that the 0.05 degree Land Evapotranspiration Dataset for the Qinghai-Tibet Plateau (LEDQTP) has the highest temporal correlation coefficient (0.80) and the smallest root-mean-square error (23.50 mm) compared to the observations. Based on LEDQTP, we find precipitation is the main influencing factor of ET, which primarily affects ET through direct pathway in bare soil and grassland regions with standardized estimates of 0.521 and 0.606, respectively. However, in meadow, shrub and forest regions, the primary factor influencing ET is air temperature, which is primarily by indirect pathway through affecting vapor pressure deficit. Air temperature is also the controlling factor in sparse vegetation region, but it affects ET through direct pathway. This study may provide some new useful information on the effects of climate change on ET in different land cover types over the TP.